2017
DOI: 10.3389/fimmu.2017.00446
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Responses Regulating Alveolar Ion Transport during Pulmonary Infections

Abstract: The respiratory epithelium is lined by a tightly balanced fluid layer that allows normal O2 and CO2 exchange and maintains surface tension and host defense. To maintain alveolar fluid homeostasis, both the integrity of the alveolar–capillary barrier and the expression of epithelial ion channels and pumps are necessary to establish a vectorial ion gradient. However, during pulmonary infection, auto- and/or paracrine-acting mediators induce pathophysiological changes of the alveolar–capillary barrier, altered ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 106 publications
3
52
0
Order By: Relevance
“…These exposed areas can be covered by basement membrane elements such as fibrin and fibrinogen deposition, laminin, or type I and IV collagen. This phenomenon has been observed in the clinics; patients can be easily infected by bacteria while recovering from primary illness (Louria et al, 1959 ; Peteranderl et al, 2017 ). In addition, many bacterial virulence factors can attach to elements of the extracellular matrix or basement membrane (Foster and Hook, 1998 ; McCullers and Tuomanen, 2001 ).…”
Section: Influenza Infection Increases Host Susceptibility To Bacterimentioning
confidence: 86%
“…These exposed areas can be covered by basement membrane elements such as fibrin and fibrinogen deposition, laminin, or type I and IV collagen. This phenomenon has been observed in the clinics; patients can be easily infected by bacteria while recovering from primary illness (Louria et al, 1959 ; Peteranderl et al, 2017 ). In addition, many bacterial virulence factors can attach to elements of the extracellular matrix or basement membrane (Foster and Hook, 1998 ; McCullers and Tuomanen, 2001 ).…”
Section: Influenza Infection Increases Host Susceptibility To Bacterimentioning
confidence: 86%
“…To check if lncRNA-ACOD1 functions through apoptosis and autophagy, which are reported to be involved in viral clearance (25,26), we tested the effect of lncRNA-ACOD1 with flow cytometry and immunoblot assay and found that host-cell apoptosis and autophagy were not influenced by lncRNA-ACOD1 ( fig. S13).…”
mentioning
confidence: 99%
“…The activation of TNF receptor 1 by TNF modulates the integrity of the alveolar barrier, in addition to its direct effects on ion channels and pumps of the alveolar epithelium. TNF increases the endothelial expression of chemo-attractants and adhesion molecules including IL-8 (formerly called neutrophil chemotactic factor), the IL-8- receptor 2, the intercellular adhesion molecule-1 (ICAM-1), platelet endothelial cell adhesion molecule-1 (PECAM-1), and vascular adhesion molecule-1, thus promoting excessive recruitment of mononuclear phagocytes and neutrophils during lung inflammation ( 71 , 369 – 371 ).…”
Section: Cytokine-ion Channel Interactionmentioning
confidence: 99%